Plasmodium vivax chloroquine resistance links to pvcrt transcription in a genetic cross - Juliana M. Sá (Nature Portfolio, 2019)
Here, a cross of Plasmodium vivax malaria parasites links a chloroquine resistance (CQR) phenotype to a 76 kb region of chromosome 1 and greater expression of pvcrt, an ortholog of the Plasmodium falciparum CQR transporter gene.